Influence of the Flexible Liposomes on the Skin Deposition of a Hydrophilic Model Drug, Carboxyfluorescein: Dependency on Their Composition - Mohamed Badran; Khaled Shalaby; Abdullah Al-Omrani (The Scientific World Journal)
This study focuses on the effect of different flexible liposomes containing sodium cholate, Tween 80, or cineol on skin deposition of carboxyfluorescein (CF). Size distribution, morphology, zeta potential, and stability of the prepared vesicles were evaluated. The influence of these systems on the skin deposition of CF utilizing rat skin as membrane model was investigated. Results showed that all of the investigated liposomes had almost spherical shapes with low polydispersity (PDI < 0.3) and particles size range from 83 to 175 nm. All liposomal formulations exhibited negative zeta potential, good drug entrapment efficiency, and stability. In vitro skin deposition data showed that flexible liposomes gave significant deposition of CF on the skin compared to conventional liposomes and drug solutions. This study revealed that flexible liposomes, containing cineole, were able to deliver higher amount of CF suggesting that the hydrophilic drugs delivery to the skin was strictly correlated to the vesicle composition.